HPLC Method of Determination of Methotrexate in Human Serum - NAGULU, M.; UDAY KIRAN, V.; RAMA KRISHNA, D. (Asian Journal of Chemistry, 2010)
This study described a simple and fast HPLC method for the determination of methotrexate (MTX) in serum samples were collected from adult cancer patients receiving 60 mg/m2 dose of methotrexate at Mahathma Gandhi Memorial Hospital (Warangal, India) at various time intervals after the end of each infusion. Serum was deproteinized with trichloroacetic acid and the supernatant was injected into a 250 × 4.6 mm octadecylsilane column. Mobile phase was made of tris-phosphate buffer (pH 5.7):methanol:acetonitrile (70:20:10) with a flow rate of 1 mL/min. Ultraviolet detection was done at 313 nm at ambient temperature. p-Aminoacetophenone was used as internal standard. Methotrexate and internal standard retention times were 4.6 and 9.5 min, respectively. Results showed that reproducibility (precision) of method within a day was 2.6 to 6.0 % and between days was 5.5 to 9.5 %. The recovery of the method was between 61.5 and 72.7 %. The quantitation limit of the method for methotrexate was 0.1 μM. This method is suitable for quantitation of methotrexate after infusion of 60 mg/m2 doses of this drug and has good accuracy, precision and quantitation limit.